From Metabolism to Vitality: Uncovering Riboflavin’s Importance in Poultry Nutrition - Yauheni Shastak; Wolf Pelletier (Animals, 2023)
Riboflavin, or vitamin B2, is indispensable for poultry, profoundly impacting their metabolic equilibrium, growth, and overall health. In a climate of increasing demand for poultry products and heightened production intensity, grasping the multifaceted roles of riboflavin in domestic fowl nutrition becomes paramount. This essential vitamin serves as a precursor to two vital coenzymes, flavin mononucleotide and flavin adenine dinucleotide, integral players in pivotal redox reactions and energy metabolism. Inadequate riboflavin levels translate into stunted growth, skeletal deformities, and compromised feed conversion efficiency, thereby adversely affecting poultry performance and bottom-line profitability. Riboflavin goes beyond its fundamental role, ameliorating nutrient utilization, facilitating protein synthesis, and augmenting enzyme activity, rightfully earning its epithet as the “growth-promoting vitamin”. Poultry’s reproductive success intricately hinges on riboflavin levels, dictating egg production and hatchability. It is imperative to note that riboflavin requirements exhibit variations among poultry species and distinct production phases, emphasizing the importance of judicious and balanced supplementation strategies. Aligning dietary recommendations with genetic advancements holds the promise of fostering sustainable growth within the poultry sector. Exploring the multifaceted aspects of riboflavin empowers researchers, nutritionists, and producers to elevate poultry nutrition and overall well-being, harmonizing with the industry’s evolving demands.